Peramalan jumlah pasien dengan diagnosa acute upper respiratory infection menggunakan metode autoregressive integrated moving average (ARIMA) pada Klinik Pratama Mitra Sehat - Saputra, Berlian Harry; Afifah, Shafa Nur; Indahsari, Annisa; Yonathan, Andrean; Simanjuntak, Anggiat Wickhern Jones (Prosiding Seminar Nasional Matematika dan Pendidikan Matematika, 2021)
Acute upper respiratory infection is the most common disease suffered by patients at the Pratama Mitra Sehat clinic. During the last 2.5 years, the number of patients suffering from acute upper respiratory infection has reached 12875 people. Some of the diseases included in this infection are colds, sinusitis, tonsillitis, and laryngitis. This type of disease can be transmitted through the air. The study will estimate the number of patients diagnosed with acute upper respiratory infections in the next few months. ARIMA or Autoregressive Integrated Moving Average is a forecasting method that will be used to predict the number of patients suffering from acute upper respiratory tract infections, so that in the future Pratama Mitra Sehat Clinic can prepare matters related to diagnosis. The steps for using the ARIMA method are using data from the required sample, determining the type of time series data pattern, conducting a stationarity test, determining the ARIMA model, calculating and analyzing the accuracy of the model used, then forecasting. The best ARIMA model for this forecasting based on the calculation is (2, 0, 1) with an error value 0.0389305.